DETERMINASI TAX AVOIDANCE MASA PANDEMI COVID-19 - Annisa Aulia Rahmah; Murtanto Murtanto (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
The purpose of this study is to analyze the effect of the Financial Distress toward the Tax Avoidance. To analyze the effect of the Profitability toward the Tax Avoidance. To analyze the effect of the Leverage toward the Tax Avoidance. To analyze the effect of the Sales Growth toward the Tax Avoidance. To analyze the effect of the Good Corporate Governance toward the Tax Avoidance. The sample consist of 34 data of the companies in the healthcare sector listed in Indonesia Stock Exchange for the 2019-2021 period. The data used in this study are secondary data and the method of selecting the sampling using purposive. This research use multiple regression analysis as hypothesis testing. The results showed that Financial Distress have positive significant effect on Tax Avoidance. Profitability have negative significant effect on Tax Avoidance. Leverage have insignificant effect on Tax Avoidance. Sales Growth have insignificant effect on Tax Avoidance. Good Corporate Governance have insignificant effect on Tax Avoidance.